2011
DOI: 10.1002/pat.1759
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of organo‐layered double hydroxide dispersion in LDPE‐based nanocomposites

Abstract: Low‐density polyethylene/layered double hydroxide (LDPE/LDH) nanocomposites were prepared via melt extrusion using organo‐LDH particles and maleic anhydride functionalized polyethylene as compatibilizer. Processing parameters, preparation method, and feed composition were properly modulated until obtaining nanocomposites with intercalated/exfoliated morphologies, and an uniform distribution of nanolayers, as evidenced by X‐ray diffraction and transmission electron microscopy analysis. These materials showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…In a previous work, it was found that LDPE/organo-LDH nanocomposites, prepared in a twin screw extruder, had a lower storage modulus with respect to the polymer matrix [41], not evidencing reinforcement, but rather a softening of the matrix. It was assumed that this effect could be a consequence of the low stiffness of the organo-LDH particles [66][67][68], even if it was not excluded that the free surfactant and surfactant molecules loosely bound to the outer surface of the LDH particles could increase the mobility of the polymer chains at the polymerfiller interfacial region, thus acting as plasticizers [68].…”
Section: Muksing Et Al -Express Polymer Letters Vol5 No5 (2011) 4mentioning
confidence: 95%
See 1 more Smart Citation
“…In a previous work, it was found that LDPE/organo-LDH nanocomposites, prepared in a twin screw extruder, had a lower storage modulus with respect to the polymer matrix [41], not evidencing reinforcement, but rather a softening of the matrix. It was assumed that this effect could be a consequence of the low stiffness of the organo-LDH particles [66][67][68], even if it was not excluded that the free surfactant and surfactant molecules loosely bound to the outer surface of the LDH particles could increase the mobility of the polymer chains at the polymerfiller interfacial region, thus acting as plasticizers [68].…”
Section: Muksing Et Al -Express Polymer Letters Vol5 No5 (2011) 4mentioning
confidence: 95%
“…Even though it has been demonstrated that the organic modification of LDH is sufficient to achieve the intercalation of PE chains between the layers [41], the use of a compatibilizer, such as a polyethylene functionalized with maleic anhydride groups (PEMAH), is necessary to improve the interactions between the polymer and the LDH and to favor the formation of composites with a stable morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The first is an unmodified hydrotalcite (U-HT) (Perkalite LD, Akzo Nobel, Amsterdam, The Netherlands), the second is organically modified with hydrogenated fat acids (OM-HT) (Perkalite F100S, Akzo Nobel, Amsterdam, The Netherlands, modifier content = 55 wt%). In a previous work [32], OM-HT was characterized by Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA) and it was shown that it is most likely modified with stearate and palmitate anions and the amount of adsorbed/free surfactant molecules is low (roughly 3 wt%). Tetrahydrofuran (THF) is purchased by Sigma Aldrich (St. Louis, USA).…”
Section: Experimental 21 Materialsmentioning
confidence: 99%
“…Layered double hydroxides (LDH) [7] and layered hydroxide salts (LHS) [8] belong to this family of compounds, and even though the former has been fairly well-studied, the latter is rarely found in the literature, especially when used as fillers in polymer composites [9][10][11][12][13] . For example, improvement of the thermal-oxidative degradation of LDPE and a slight increase in crystallization temperature was evidenced by Muksing et al [14] , whereas significant improvement of the thermal-oxidative stability and remarkable reduction of the oxygen permeability of LDPE was reported by Coiai et al [15] . Higher performance nanocomposites with respect to flame retardance and thermal stability are commonly attributed to a better dispersion state of the LDH in the LDPE matrix and the greater hindrance effect of LDH layers on the diffusion of oxygen and volatile products throughout the composite materials when they are exposed to burning or thermal degradation [16] .…”
Section: Introductionmentioning
confidence: 99%